Pelaksanaan Bimbingan Penyuluh Agama Islam Terhadap Calon Pengantin Guna Mewujudkan Keluarga Sakinah di Kecamatan Bendahara Kabupaten Aceh Tamiang - Kahar Muzakir (PT FORMOSA CENDEKIA GLOBAL, 2022)
This article describes the implementation of the guidance of Islamic religious educators to prospective brides in order to create a sakinah family in the Bendahara sub-district, Aceh Tamiang Regency, the purpose of writing this article is as an education for readers and Islamic religious educators to conduct a thorough evaluation so that the implementation of guidance to prospective brides the following day can be carried out. more optimally. The type of writing this article is a qualitative service that seeks to describe and describe a sincere and sincere service to the community that has been carried out and then described in a structured manner by following the rules of writing scientific papers that apply. From the results of writing this article, it is found that: First, the implementation of guidance for the bride and groom which emphasizes the character, moral and mental development of the prospective bride and groom. Second, the guidance material for the bride and groom is the rights and obligations of husband and wife, the challenges of domestic life in the future and reducing conflicts in the household. Third, marriage guidance for the bride and groom using humanist and persuasive language